Reproduction in the male cheetah Acinonyx jubatus jubatus (Schreber, 1776) - Skinner, J.D. (John Dawson), 1932- (University of Pretoria, 2013)
Dissertation (MSc (Zoology))--University of Pretoria, 2007.